2014
DOI: 10.1128/jvi.02935-13
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Deaminase Acts as a Natural Antagonist for Dipeptidyl Peptidase 4-Mediated Entry of the Middle East Respiratory Syndrome Coronavirus

Abstract: In 2012, a previously unknown human coronavirus (CoV), now named Middle East respiratory syndrome CoV (MERS-CoV), was isolated from the sputum of a 60-year-old man in Saudi Arabia who presented with acute pneumonia with a fatal outcome (1, 2). To date, several infection clusters have been reported over a 1-year period, with around 50% of the reported human cases being fatal (3). MERS-CoV represents a novel betacoronavirus species, with the closest known relatives being clade 2c bat CoVs detected in bats (4, 5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
178
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(188 citation statements)
references
References 20 publications
5
178
0
5
Order By: Relevance
“…Cockrell et al (61) found that introducing part of this region (residues 279 to 346) from hDPP4 into mouse DPP4 (mDPP4) resulted in successful infection in vitro. This result is supported by a similar experiment conducted using ferret DPP4 (fDPP4), in which swapping residues 247 to 504 of hDPP4 into the fDPP4 backbone supported MERSCoV infection (63). In addition, transfecting hDPP4 into mouse or hamster cell lines resulted in successful infection (61), suggesting that it is host cell receptor interactions that restrict MERSCoV host range, rather than the presence of other host-specific restriction factors.…”
Section: Mers-cov and Dpp4mentioning
confidence: 54%
See 1 more Smart Citation
“…Cockrell et al (61) found that introducing part of this region (residues 279 to 346) from hDPP4 into mouse DPP4 (mDPP4) resulted in successful infection in vitro. This result is supported by a similar experiment conducted using ferret DPP4 (fDPP4), in which swapping residues 247 to 504 of hDPP4 into the fDPP4 backbone supported MERSCoV infection (63). In addition, transfecting hDPP4 into mouse or hamster cell lines resulted in successful infection (61), suggesting that it is host cell receptor interactions that restrict MERSCoV host range, rather than the presence of other host-specific restriction factors.…”
Section: Mers-cov and Dpp4mentioning
confidence: 54%
“…It has been well studied due to the role it plays in glucose metabolism, immune responses, adhesion, and apoptosis (57). Whereas MERS-CoV can enter cells using DPP4 from humans, nonhuman primates, bats (58), camels, horses, and to a lesser extent goats (59,60), it is unable to enter cells using DPP4 from traditional small animal model species such as mice (61,62), ferrets (63), and hamsters (58,64). This species restriction prevents the adequate study of MERS-CoV pathogenesis and limits the development of vaccine strategies or alternate therapeutics.…”
Section: Mers-cov and Dpp4mentioning
confidence: 99%
“…70 MERS-CoV S cannot bind to DPP4 in species that have significant differences in these 14 amino acids as compared with human DPP4 (hDPP4), such as ferrets, hamsters, and mice; thus, these species are resistant to infection. 21,40,62,69 Species with few or no differences in the 14 amino acids seem to be susceptible to MERS-CoV, including rhesus macaques, common marmosets, and camels. 25,50,69 In addition to analyzing the DPP4 amino acid sequence, evaluating the binding energies between MERS-CoV and DPP4 has proven useful in assessing whether MERS-CoV S can bind to DPP4 from different species.…”
mentioning
confidence: 99%
“…17,21,62 Despite a lack of conventional small animal models, researchers have identified several other species that are susceptible to MERS-CoV infection, including rabbits, hDPP4-transduced or hDPP4-transgenic mice, rhesus macaques, and common marmosets (summarized in Tables 1 and 2). Each animal model of MERS-CoV infection is discussed in detail.…”
mentioning
confidence: 99%
“…The development of inhibitors that target the binding site and receptors (DPP4) may prove to be of benefit for the therapy of MERS-CoV infection [9]. An in vitro study of MERS-CoV infection in ferrets showed that adenosine deaminase, a DPP4 binding protein, competed for virus binding and exhibited a natural antagonist for MERS-CoV infection [9]. For the search of an effective therapy, the domains of DPP4 (CD26) were required for the binding of MERS-CoV [8,10].…”
mentioning
confidence: 99%